Landslide Susceptibility Mapping in NDUM Campus, Kuala Lumpur, Malaysia - Jestin Jelani,; Zuliziana Suif,; Nordila Ahmad,; Nik Muhammad Iqbal Hakimi Safaruddin,; Wan Mohamed Syafuan Wan Mohamed Sabri,; Rusnardi Rahmat Putra, (International Journal of Integrated Engineering, 2025)
Landslides are among the most destructive natural disasters, frequently resulting in significant loss of life as well as property each year, particularly in regions with high elevations and steep slopes. With an advanced technological approach, the integration of geographic information system (GIS) as well as remote sensing has been extensively utilised to identify areas susceptible to landslides, providing crucial insights for disaster preparedness and mitigation. This study aims to create a landslide susceptibility map (LSM) for the National Defence University of Malaysia (NDUM) campus. This study adopted the Analytic Hierarchy Process (AHP) modelled in ArcGIS 10.8 software to integrate five major landslide-induced parameters: slope angle, elevation, drainage density, soil type, and lithology. The slope angle and elevation thematic maps were obtained from the Digital Elevation Model (DEM). Lithology and drainage density data were sourced from Malaysia's Department of Mineral and Geoscience (JMG) as well as the Department of Survey and Mapping, Malaysia (JUPEM). The local soil type was obtained from the NDUM site investigation report. The resulting LSM was classified into five levels of risk zones, with 0.1%, 29.1%, 2.3%, 2.8%, and 65.7% falling under very low risk, low risk, moderate risk, high risk, as well as very high risk, respectively. The LSM was verified with a previously failed slope on the NDUM campus, showcasing good agreement for both methods. The accuracy of the landslide hazard zonation map may be enhanced by integrating additional factors, for instance, land cover, land use, rainfall, as well as other relevant elements.